Análise da atividade elétrica e do torque da musculatura abdutora do ombro em sujeitos hemiparéticos crônicos - Avila, Mariana Arias (2010)
Background: There is still a lack of evidence of how electromyographic (EMG) patterns deficits of muscle activation are related to the shoulder abduction movement in people with chronic hemiparesis. Objective: Analyze EMG patterns and isokinetic muscle performance of shoulder abduction motion in subjects with chronic hemiparesis. Design: Cross-sectional trial. Methods: Twenty five subjects with chronic hemiparesis and twenty five healthy subjects underwent EMG activity and isokinetic shoulder abduction assessments. EMG onset time and RMS were compared between limbs (intra-group) and between groups (inter-group) for trapezius and deltoid muscles. Isokinetic peak torque, total work, average power and acceleration time were also compared intra- and inter-groups. Results: The paretic side showed an opposed onset activation pattern in shoulder abduction, along with a lower RMS for both muscles. The non-paretic side showed a delay in both muscles activation and a lower RMS for the trapezius, compared to the control group. Both sides of the group with hemiparesis presented a significantly lower isokinetic performance compared to the control group. Conclusions: Trapezius and middle deltoid muscles activation, as well as torque, speed and endurance are altered in both paretic and non-paretic shoulders in subjects with chronic hemiparesis. The non-paretic limb is less affected than the paretic one. These facts should be taken into account in the rehabilitation program after stroke.